Protective effects of gallic acid on cardiac electrophysiology and arrhythmias during reperfusion in diabetes - Ramezani-Aliakbari, Fatemeh (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): Gallic acid (GA), a potent anti-oxidant, plays an important role in reducing diabetic induced cardiac disorders. Therefore, the present investigation was purposed to determine the beneficial effect of GA in cardiac arrhythmias during reperfusion in diabetes induced by alloxan. MATERIALS AND METHODS: Male Sprague-Dawley rats (200–250 g) were randomly divided into three groups (eight in each group): control (C), diabetic (D), and diabetic treated with GA (D+G) groups. GA was administered by gavage (25 mg/kg, daily) for eight weeks. Diabetes was induced by a single intraperitoneal injection of alloxan (120 mg/kg). Ischemia-reperfusion (IR) injury was performed by ischemia and then reperfusion (30 and 120 min, respectively). The score and magnitude of arrhythmias, creatine kinase (CK-MB), and lactate dehydrogenase (LDH) of the heart, electrocardiographic, and hemodynamic parameters were measured. One-way ANOVA followed by LSD tests were used for the differences between groups. The percentage of incidence was also evaluated by Fisher’s exact test. RESULTS: The duration (P<0.05), onset (P<0.01), score and incidence of arrhythmia, QT interval (P<0.001), LDH, and CK-MB (P<0.05) were significantly elevated and the contractility of the heart (±dp/dt, P<0.01), LVSP, QRS complex voltage (P<0.05), and heart rate (P<0.01) were significantly reduced in the diabetic animals compared with the control rats. However, administration with GA significantly improved these alterations in the diabetic group compared with the diabetic animals. CONCLUSION: This study indicated the beneficial effects of GA on cardiac electrophysiology and arrhythmias during reperfusion in diabetes.